Quantenstochastik: 25.1. bis 31.1.1987 - Accardi, Luigi; Waldenfels, Wilhelm von (Tagungsbericht, 1987)
L. Accardi, Roma; D. Applebaum, Nottingham; A. Barchielli, Milano; V. Cantoni, Milano; V. Cantoni, Milano; C. Cecchini, Genova; W. Cegla, Wroclaw; M. F. Chen, Beijing; F. Fagnola, Povo; M. Fannes, Leuven; G. W. Ford, Ann Arbor; A. Frigerio, Milano; V. Gorini, Milano; G. C. Hegerfeldt, Göttingen; H. Heyer, Tübingen; A. S. Holevo, Moscow; R. L. Hudson, Nottingham; R. Jajte, Lodz; B. Kümmerer, Tübingen; J. T. Lewis, Dublin; G. Lindblad, Stockholm; J. M. Lindsay, London; A. Luczak, Lodz; H. Maassen, Nijmegen; P. A. Meyer, Strasbourg; K. R. Parrhasarathy, New Delhi; D. Petz, Budapest; S. Pirogov, Moscow; J. Quaegebeur, Leuven; U. Quasthoff, Leipzig; M. Remenyi, Heidelberg; J. L. Sauvageot, Paris; M. Schürmann, Heidelberg; G. L. Sewell, London; K. B. Sinha, New Delhi; R. F. Streater, London; G. Süßmann, München; Y. Suhov, Moscow; K. Urbanik, Wroclaw; A. Verbeure, Leuven; G. Vincent-Smith, Oxford; W. von Waldenfels, Heidelberg; I. F. Wilde, London; M. Wolff, Tübingen
Beitr. in engl. Sprache